Study on emergency response model during construction of Sichuan-Tibet Railway. Issue 1 (February 2021) - Cui, Yunxiao; Zhi, Danyue; Lv, Ying
Abstract: During the construction of The Sichuan-Tibet railway, there is a risk of sudden natural disasters. Rapid and effective rescue to the affected areas can reduce casualties and property losses. Based on the interval planning theory, this paper studies the emergency rescue plan in the construction of Sichuan-Tibet railway considering the coordinated rescue of various transportation modes. We constructs a two-stage model of distributing relief materials to the disaster areas and bringing the injured back to the facilities. In the first stage, the facility storage centre point responsible for rescue is decided, and the facility storage centre point opening scheme that conforms to the constraints of the actual time window is obtained. The second stage logistics vehicle distribution problem, to the disaster areas to deliver relief supplies and bring back the injured, the optimized distribution route plan. Finally, an example analysis is carried out to verify the feasibility of the model by solving GAMS.